Implementasi Material Berkelanjutan pada Interior Gedung Bina Graha Kementerian Lingkungan Hidup dan Kehutanan (KLHK) di Jakarta Selatan) - Harahap, Rachmita Maun; Lelo, Lelo; Basyiroh, Anis Ainissyifa Wardatul (Program Studi Desain Interior Unikom, 2024)
In the era of environmental uncertainty in the use of sustainable materials in terms of material fulfillment and increasing concern for sustainability, the Ministry of Environment and Forestry (MoEF) building play an important role in implementing national habitat and forestry environmental policies and programs. However, based on the result of observation and interview, it was found that the problem of the interior materials are not in accordance with the MoEF's planned environmental approach. The purpose of this study is to examine the requirements of ecological materials suitable for the interior for the MoEF building, to create a sustainable interior by incorporating ecological materials, and to increase awareness and understanding of environmental materials among interior designers and other stakeholders. The research method used was a qualitative method with a phenomenological approach. Data collection focused on designers' attitudes towards eco-friendly design. Limitations of this study include the emphasis on the adoption of sustainable interior materials only, without any major changes to the structure. This research considers the technical, economic, and aesthetic aspects of ecological material selection. It also provides practical guidance on how to reduce environmental impact through the use of ecological materials in interiors, creating a more sustainable interior environment. Keywords : ecology, environmentally friendly, interior material, KLHK graha building, sustainable